2020
DOI: 10.3390/ijms21093318
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Patterns and Geographical Parthenogenesis in the Alpine Plant Species Ranunculus kuepferi (Ranunculaceae)

Abstract: Polyploidization and the shift to apomictic reproduction are connected to changes in DNA cytosine-methylation. Cytosine-methylation is further sensitive to environmental conditions. We, therefore, hypothesize that DNA methylation patterns would differentiate within species with geographical parthenogenesis, i.e., when diploid sexual and polyploid apomictic populations exhibit different spatial distributions. On natural populations of the alpine plant Ranunculus kuepferi, we tested differences in methylation pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 98 publications
(192 reference statements)
3
16
0
Order By: Relevance
“…In case this phenotypic variation is heritable, DNA methylation could provide a mechanism of adaptive microevolution in plants [ 36 , 104 ], which is faster and independent from traditional genetic evolution [ 88 , 105 , 106 ]. Epigenetic variation differed in R. kuepferi between cytotypes, and also varied under climatic conditions, both in natural populations [ 68 ] and under controlled conditions [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In case this phenotypic variation is heritable, DNA methylation could provide a mechanism of adaptive microevolution in plants [ 36 , 104 ], which is faster and independent from traditional genetic evolution [ 88 , 105 , 106 ]. Epigenetic variation differed in R. kuepferi between cytotypes, and also varied under climatic conditions, both in natural populations [ 68 ] and under controlled conditions [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…A molecular dating revealed that the tetraploid cytotype originated only 10–80 thousand years ago [ 66 ], probably via multiple and recurrent polyploidization events [ 61 , 67 ]. Epigenetic studies using methylation-sensitive amplified fragment-length polymorphisms (MS-AFLPs) on the species suggested differential profiles in the cytotypes and a connection to abiotic environmental conditions of the epigenetic variation in natural populations and experimental treatments [ 68 , 69 ]. This epigenetic variation was further correlated with an elevation in natural populations [ 68 ] and showed higher persistence under cold treatment in experimental conditions [ 69 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, observed variability of proportions of facultative apospory under different light stress conditions in hexaploid clone-mates of R. carpaticola × cassubicifolius , including residual levels in diploid and tetraploid cytotypes, suggests an influence of epigenetic regulatory mechanisms on reproductive phenotypes [ 45 , 46 ]. In R. kuepferi , differential cytosine-methylation patterns found in sexual and apomictic natural populations support this hypothesis [ 94 ]. In other apomictic plant groups different genes had been found linked to the apomixis phenotype or to individual components of apomixis (e.g., [ 95 , 96 , 97 , 98 , 99 , 100 , 101 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, epigenetic control mechanisms may play a role. A study on cytosine methylation of diploid and tetraploid R. kuepferi revealed not only different methylation profiles between cytotypes, but also indicated two different epigenetic groups within tetraploids, correlating with different temperature exposures [ 69 ].…”
Section: Discussionmentioning
confidence: 99%